Menanamkan Karakter Ikhlas Sejak Usia Dini: Pembentukan Keikhlasan pada Anak PAUD KB Hidayatullah Gading Kulon Banyuanyar Probolinggo sebagai Landasan Kebaikan - Husni Atil Warda; Ainur Rofiq Sofa (Sekolah Tinggi Agama Islam Yayasan Pendidikan Ilmu Qur'an Baubau, 2025)
Early Childhood Education (PAUD) plays a crucial role in shaping children's character and personality. One of the essential character values to instill from an early age is sincerity. The instillation of sincere character in PAUD children forms positive social and spiritual attitudes, which will affect their development in the future. This study aims to examine the application of sincerity values in character building for children at PAUD KB Hidayatullah Gading Kulon Banyuanyar Probolinggo. The research method used is a qualitative approach with interviews and observations as data collection techniques. The results show that PAUD KB Hidayatullah has integrated sincerity values into learning activities, both in religious education and daily social interactions. Sincerity is understood as performing good deeds with pure intentions for Allah alone, without expecting praise or reward. The instillation of this value has positively impacted the children's character development, including strengthening empathy, cooperation, and a sense of responsibility. Based on these findings, it is recommended that sincerity values be more widely integrated into the PAUD curriculum to create a generation that is not only intellectually capable but also morally upright.